DESKRIPSI PENGETAHUAN SUAMI TENTANG GENDER DAN PERAN SUAMI DALAM MENDUKUNG PENGGUNAAN ALAT KPNTRASEPSI PADA IBU AKSEPTOR KB DI PONDOK BERSALIN â€œDOA IBUâ€ KABUPATEN REMBANG - Woro Tri Utami, Woro Tri Utami (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2014)
The difference of concept and understanding about gender socially has born difference role of man and woman in society, including role of man and woman in family planning program. The purpose of this research was to describe of husband knowledge about gender and role of husband in supporting usage of contraception device at mother who was an acceptor of family planning in ?Doa Ibu? Birthing Centre Sub Province of Rembang. The methode that is used in this research was survey descriptive with husband of mother who was an acceptor of family planning in ?Doa Ibu? birthing centre at period of May 2014 as the population. The amount of sample was 30 people, taken by accidental sampling. The result of this research show the husband knowledge about gender was included in category good enough (53,33%). Role of husband including in good category in giving support usage contraception device to his wife (93,67%).Respondents expected to be more active in seeking information about understanding of gender which not yet precisely in society and increase in supporting his wife usage contraception device according to an ideal condition that expected from couple who was an acceptor of family planning program.Keywords: Knowledge , Gender, Role of Husband, Contracetion Device